Weak-coupling to strong-coupling quantum criticality crossover in a Kitaev quantum spin liquid α-RuCl3 - Jae-Ho Han; Seung-Hwan Do; Kwang-Yong Choi; Sang-Youn Park; Jae-You Kim; Sungdae Ji; Ki-Seok Kim; Jae-Hoon Park (npj Quantum Materials, 2023)
Abstract We report a quantum criticality crossover representing two different universal scaling behaviors in a Kitaev quantum magnetic material α-RuCl3. α-RuCl3 presents both a symmetry-breaking antiferromagnetic order and a long-range entangled topological order of a quantum spin liquid, and thus could be a candidate system for a unique universality class involving deconfined fractionalized excitations of the local Z2 fluxes and itinerant Majorana fermions. Theoretical analyses on the inelastic neutron scattering, ac-magnetic susceptibility, and specific heat results demonstrate that Wilson–Fisher-Yukawa-type ‘conventional’ weak-coupling quantum criticality in high-energy scales crosses over to heavy-fermion-type ‘local’ strong-coupling one in low-energy scales. Our findings provide deep insight on how quantum criticality evolves in fermion-boson coupled topological systems with different types of deconfined fermions.